Comparative assessment of width of neutral zones recorded using two neutral zone impression methods (phonetic and swallowing) and two different materials (tissue conditioner and polyether): A crossover pilot study - Manjita M Parab; Meena A Aras; Vidya Chitre; Anchal Qanungo (Wolters Kluwer Medknow Publications, 2021)
Statement of Problem: Medium body polyether impression material has been recently used as neutral zone recording material. However, there is a lack of studies comparing it with routinely used material. Purpose: The purpose of the study is to compare neutral zone width of phonetic (PNZ) and swallowing (SNZ) neutral zone impression techniques with a tissue conditioner and a polyether impression material within the same subjects. Materials and Methods: Assessments of neutral zone width were carried out in ten completely edentulous patients with advanced mandibular resorption. On each patient, four neutral zone impressions were recorded as follows: SNZ with tissue conditioner material, PNZ with tissue conditioner material, SNZ with polyether impression material, PNZ with polyether impression material. Putty indices were made of each neutral zone and traced on graph paper. The buccolingual measurements were made at five different locations, midline, right first premolar, left first premolar, right first molar, and left first molar. Statistical analysis was done using Mann-Whitney U test. Results: There was no significant difference observed when comparison was done either between materials or techniques. Conclusion: Medium body polyether can be a viable alternative to conventional tissue conditioner material and can be used with both swallowing and phonetic techniques with equal efficacy.